Penyuluhan Makna Filosofis Banten Bayekala Hari Raya Penampahan Galungan Pada WHDI Provinsi NTB - Ni Komang Wiasti (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
Banten is a Vedic language that is rich in symbols and has a deep spiritual meaning so it is needed as a means of supporting the Panca Yadnya ritual ceremony. One of the functions of the offering as a cleansing agent is the banten bayekala which is used to purify the bhur realm (niskala) and as an outward purification. The use of banten bayekala is not widely understood by the Hindu community, especially in West Nusa Tenggara. Therefore, the Women of Hindu Dharma Indonesia, West Nusa Tenggara Province, held a coaching activity on the philosophical meaning of Banten Bayekala on Galungan Day. Because on the day of Penampahan Galungan, all Hindus are Natab Banten Bayekala as a neutralizer of bad qualities (sad ripu) that exist in a person.